1985
DOI: 10.1093/nar/13.3.985
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence of a cluster of early and late genes in a conserved segment of the vaccinia virus genome

Abstract: The nucleotide sequence of a 7.6 kb vaccinia DNA segment from a genomic region conserved among different orthopox virus has been determined. This segment contains a tight cluster of 12 partly overlapping open reading frames most of which can be correlated with previously identified early and late proteins and mRNAs. Regulatory signals used by vaccinia virus have been studied. Presumptive promoter regions are rich in A, T and carry the consensus sequences TATA and AATAA spaced at 20-24 base pairs. Tandem repeat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
0

Year Published

1986
1986
1998
1998

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(64 citation statements)
references
References 18 publications
(20 reference statements)
5
59
0
Order By: Relevance
“…In vaccinia virus this conserved region encodes a set of mainly late genes (Plucienniczak et al, 1985) and many of the FPV sequences 5' to the ORFs closely resemble the consensus sequence AA AA rr TAAAT~ which has been proposed for vaccinia virus late promoters (Hanggi et al, 1986). A comparison of the probable promoter sequences present 5' to the genes in FPV and vaccinia virus is presented in Fig.…”
Section: Identification Of the Conserved Regionmentioning
confidence: 77%
See 3 more Smart Citations
“…In vaccinia virus this conserved region encodes a set of mainly late genes (Plucienniczak et al, 1985) and many of the FPV sequences 5' to the ORFs closely resemble the consensus sequence AA AA rr TAAAT~ which has been proposed for vaccinia virus late promoters (Hanggi et al, 1986). A comparison of the probable promoter sequences present 5' to the genes in FPV and vaccinia virus is presented in Fig.…”
Section: Identification Of the Conserved Regionmentioning
confidence: 77%
“…The conservation of ORFs FP1 to FP9 in FPV suggests that these proteins are translated in both FPV and vaccinia virus. Plucienniczak et al (1985) reported homologies between F2 and variable surface glycoprotein 3 of Trypanosoma brueei, F4 and VP2 of foot-and-mouth disease virus and VP1 of poliovirus, and F9 with anthranilate synthase from E. coli and Neurospora erassa. All of the FPV ORFs have been compared with the National Biomedical Research Foundation databases using FASTP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After the construction of restriction maps (Wittek et al, 1977;Mackett & Archard, 1979) and the cloning of individual restriction fragments (Wittek et al, 1980;Belle Isle et al, 1981), the 186kb genome of the laboratory strain of vaccinia virus (Western Reserve, WR) has been studied in detail. The structure of the terminal hairpins has been determined and the complete sequence of several of the viral HindIII restriction fragments and many individual genes have been reported from WR and other strains of virus (Ahn et al, 1990;Amegadzie et al, 1991;Baldick & Moss, 1987;Boursnell et al, 1988;Bertholet et al,, 1985;Broyles & Moss, 1986;Earl et al, 1986;Gillard et al, 1986;Gordon et al, 1988;Hirt et al, 1986;Howard & Smith, 1989;Howard et al, 1991 ;Jin et al, 1989;Kotwal & Moss, 1988aNiles et al, 1986;Plucienniczak et al, 1985;Rodriguez et al, 1986;Rodriguez & Esteban, 1987;Rosel et al, 1986;Rosel & Moss, 1985;Roseman & Hruby, 1987;Roseman & Slabaugh, 1990;Schmitt & Stunnenberg, 1989;Slabaugh & Roseman, 1989;Slabaugh et al, 1988;Shida, 1986;Smith et al, 1989a, b, c;Smith & Chan, 1991;Tamin et al, 1988;Tengelsen et al, 1988;Traktman et al, 1989;Tsoa et al, 1986;…”
Section: Introductionmentioning
confidence: 99%